Vous êtes sur la page 1sur 2

L V L L

L A = (S, s 0 , ., S )

(s 1 , s 2 ) S 2 s 1

E s 1 ,s 2 = {v V , s 1 .v = s 2 }

E s 1 ,s 2 s S

L s = {v V , s S , s.v = s }

A s = (S, s, ., S )

δ s,S = s S

L = L s 0

= s 2

L s =

s 2 S−{s}

E s,s 2 .L s 2 + δ s,S

V

L 1 L 2 V

X = L 1 .X

+ L 2

X V ∧ ∈/ L 1 (1) X = L .L 2 ∧ ∈ L 1 (1) {L .L, L 2 L}

1

1

X X = L 1 .X + L 2 = L 1 .(L 1 .X +

+ L 1 + ).L 2

L 2 ) + L 2 = L 2 .X + L 1 .L 2 + L 2 = L 2 .(L 1 .X + L 2 ) + L 1 .L 2 n N

+ L 2 = L 3 .X + (L 2

1

1

i

L

1

1

1

X

n

= L n+1 .X + L 2 .

1

i=0

n N L

1

= nN L 1 L .L 2 X

1

∧ ∈/ L 1

m X, |m| = n m L n+1 .X n m L .L 2

X

n N m L n , |m| ≥ n

m L 1 , |m| ≥ 1

1

1

1

L .L 2 L .L 2 X

1

1

L 1 .(L .L 2 ) + L 2 = L .L 2 + L 2 = (L

1

1

1

+

).L 2 = L .L 2

1

∧ ∈ L

1

L

L 1 .(L .L) + L 2 = L + .(L 2 + L ) + L 2 =

X

=

1

L 1

X

= (L 1 − {∧}).X + X + L 2

L 2 )

=

L .L L 2

1

L

= L .L 2 + L .L

1

1

1

=

=

L

L

1

2

2

 + X + L

L .L

1

X

L 2

X

(L 1 − {∧}) (X +

L

L

1

L +

1

L

1

L 1 .(L .L) + L 2

1

1

L + .L 2 + L + .L + L 2 = L .L 2 + L + .L ∧ ∈ L 1

= L

1

= L .L

1

= {L .L, L 2 L}

1

n

N

E i,j i, j

[1, n] 2

L i =

n

j=1

E i,j .L i + F i i[1,n]

F i i [1, n] n

L i E i,j F i L i

A = (S, s 0 , ., S ) s S

L s =

s 2 S−{s}

E s,s 2 .L s 2 + δ s,S

∧ ∈/ E s,s 2 E s,s 2 L s 0

L

0 = a.L 0 + b.L 1 +

L 1 = b.L 0 + a.L 2

L 2 = a.L 1 + b.L 2

b
a
b
a
s 0
s 1
s 2
b
a

L 2 = b aL 1 L 2 L 1 = ab aL 1 +bL 0 L 1 = (ab a) bL 0 L 1 L = L 0 = (a + b(ab a) b)